Traffic Noise in Lahore City, Pakistan. Part II. Vehicular Contribution to Traffic Noise (Biological Sciences - PJSIR, 2006)
A traffic noise survey conducted in Lahore city, Pakistan showed that the prevailing traffic noise levels were excessively high and much above the community annoyance limits. Therefore, in order to have an assessment of the level of noise emitted by different types of vehicles plying on the roads in Lahore city, measurement of the level of noise emitted from individual cars, motorcycles, vans, buses, autorickshaws and trucks was carried out in their normal V99 running condition. The data collected have been analyzed for the range of noise emission levels, L , L V90 , L V50 , L V10 V1 and L   values for each category of vehicles. Due to the lack of proper regulatory laws to limit emission of high levelnoise from individual vehicles in Pakistan, the results are discussed with reference to the vehicular noise emission limits recommended by the Council of European Economic Community, and some other individual countries. Some means and ways to limit the emission of high-level noise from individual vehicles are also suggested.